Quantitative and Qualitative Social Responsibility Disclosure Case Study of Qatar Petroleum 2008-2019 - Mohamed Boulesnam; Chaouki Kebtan (Journal of North African Economies, 2025)
In the last two decades, corporate social responsibility disclosure becomes a prominent subject due to its influence in social responsibility accounting. This study, basically, aims to identify the different quantitative and qualitative methods of social responsibility disclosure in the annual report of Qatar Petroleum during 2008-2019. After the use of content analysis and social index, the study concluded that Qatar Petroleum attempts to balance the quantitative and the qualitative methods of disclosure for the sake of improving social transparency and supporting corporate governance. Hence, the level of CSRD in Qatar Petroleum is changing over time in terms of structure and size.